Network security, firewalls, and VPNs - Stewart, James Michael (Jones & Bartlett Learning Information systems security & assurance series, 2014)
This fully revised and updated second edition provides a unique, in-depth look at the major business challenges and threats that are introduced when an organization's network is connected to the public Internet. It provides a comprehensive explanation of network security basics, including how hackers access online networks and the use of Firewalls and VPNs to provide security countermeasures. Using examples and exercises, this book incorporates hands-on activities to prepare the reader to disarm threats and prepare for emerging technologies and future attacks. Topics covered include: the basics of network security--exploring the details of firewall security and how VPNs operate; how to plan proper network security to combat hackers and outside threats; firewall configuration and deployment and managing firewall security; and how to secure local and internet communications with a VP